Adjektive mit Negationspräfixen im heutigen Dänisch - Rajnik, Eugeniusz (Folia Scandinavica Posnaniensia, 2016)
The article offers a classification of adjective prefixes in Danish (section 3) including, among others, native and foreign prefixes (e.g. gen- and a-, respectively), genuine prefixes (e.g. ægte-) and particle prefixes (e.g. anti-). Various definitions of prefixal derivatives have been presented in section 4, while section 5 shows examples of and discusses native and foreign negative prefixes modifying the meanings of adjectives in contemporary Danish. The adjectives in question have been analyzed with regards to their structure and the emotional load they convey. Section 6 concludes the paper and includes comments on the productivity of the prefixes in question, as well as synonymy and antonymy in their usage.